Design and Development Website English Learning for Elementary School to Increase Engagement - Descandra, Vianneza Alifz; Kukuh, Anang (LPPM STIKI Malang, 2024)
The development of technology has a great influence on the development of Learning media is one of the factors that plays an important role during the learning process especially for elementary school. Elementary school currently use gadget media as a daily guide but are not used as a medium for learning English. This causes a decrease in value and a lack of interest in learning English through book media due to the lack of enjoyable interaction. The purpose of this study is to find out how to design and build English learning media and increase engagement for elementary school in grade 4 based on a website that can increase interest in learning and help the teaching and learning process to be more efficient. This learning media is designed with several features such as materials, sample questions, learning videos, and practice questions which are expected to motivate students to continue to understand the learning materials obtained. The steps used in building this website are through planning needs then system design then system development and the last is implementation. This study uses Cognitive Engagement type engagement which means involvement in cognitive. With the system on the website, it is expected to help 4th grade elementary school students in English learning activities.